The Need for Social Considerations in SDG 14 - Haward, Marcus; Haas, Bianca (Frontiers in Marine Science, 2021)
Sustainable Development Goal 14 acknowledges the need for action to achieve a sustainable future for our ocean. Many initiatives are working on ocean-related issues; however, social problems are often overlooked. In this article, we argue that to achieve a sustainable ocean, social aspects need to be considered. We explore the link between SDG 14 and SDG 8 as labor and working conditions on fishing vessels receive increasing attention. Regional Fisheries Management Organizations have the mandate to manage fisheries at the high seas, therefore, we argue that these organizations need to act on, and implement, resolutions and measures, addressing labor standards. Labor conditions related to the fishing sector have not received the level of scholarly attention that they deserve, thus more research is needed.